Effect of zinc priming on zinc concentration of germinating rice seed - Prom-U-Thai,C. (Chiang Mai University, 2015)
Zinc (Zn) in rice seed is important for its germination as well as to nutrition of rice eaters. The present study evaluated the effect of zinc priming, a pre-treatment of Zn of rice seed in 5 mM ZnSO4.7H2O for 60 minutes, on its subsequent germination. The priming increased Zn concentration of whole rice seed by 3-4 fold, but not in the caryopsis (brown rice). The concentration of Zn in primed seed decreased after one day of germination and continued to decline from D2-D7, while it remained unchanged in unprimed seed for entire germination period. The density of Zn after priming with 5 mM could be monitored by the intensity of DTZ staining, when compared with those without Zn priming. As germination proceeded Zn concentration of the husk declined while that in the caryopsis increased (r= 0.61, P< 0.05). At the end of germination period, Zn concentration in the seed, coleoptiles and root of primed seed was 4.0, 1.6 and 2.0 fold higher than those from unprimed seed, respectively. Better growth of seedlings grown from seed primed with Zn was shown by dry weight of the coleoptiles and roots which was 0.80 and 1.02 mg seed-1 in primed seed and 0.60 and 0.83 mg seed-1 in unprimed seed, respectively. The results showed how priming rice seed with Zn effectively enhanced Zn concentration in rice seed as well as and improved Zn nutrition of coleoptiles and roots, suggesting a useful method to improve germination and seedling vigor, especially in rice seed that is low in Zn.